Microfoundations for Open Innovation: is effectuation a valid approach for open innovation managers? (Revista Gestão & Conexões, 2013)
DOI: http://dx.doi.org/10.13071/regec.2317-5087.2013.2.1.4968.94-115.Since Chesbrough (2003) first coined the concept of open innovation, it has attracted a growing attention in academia and practice. Academic research has spread its focus into topics such as innovation management, business strategy, organizational behavior and public policies, while practitioners have explored the concept of open innovation in diversified ways. Taking this into account, this article proposes microfoundations for open innovation by relating it to effectuation theory, originally developed in the field of entrepreneurship. Our aim is to show that effectuation theory can provide strong contribution to build a consistent micro level conceptual basis for open innovation practices.